Advertising and its place in the system of marketing in Ukraine - Myna, Zhanna; Blaha, Tatiana; Biletska, Natalia (Видавництво Львівської політехніки, 2016)
In this article we will discuss advertising as a way to solve marketing problems in Ukraine.
Keywords: e-advertising; marketing; marketing communications; goods; services